Application of the Total Productive Maintenance to Increase the Overall Value of Equipment Effectiveness on Ventilator Machines - Hibarkah Kurnia; Andini Putri Riandani; Tri Aprianto (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2023)
This article has been corrected. Please see the https://josi.ft.unand.ac.id/index.php/josi/announcement/view/41 for details.